2019
DOI: 10.1016/j.neuron.2019.09.003
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR-Cas9 Screens Identify the RNA Helicase DDX3X as a Repressor of C9ORF72 (GGGGCC)n Repeat-Associated Non-AUG Translation

Abstract: Highlights d Genome-wide CRISPR-Cas9 screens identify regulators of DPR protein production d The RNA helicase DDX3X suppresses RAN translation of C9ORF72 (GGGGCC)n repeats d Elevating DDX3X expression decreases DPR levels in C9ORF72-ALS patient cells d Elevating DDX3X rescues pathological features and improves survival of patient iPSNs

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
132
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(147 citation statements)
references
References 73 publications
13
132
2
Order By: Relevance
“…Several of the identified genes have been previously linked to the pathogenesis of parkinsonisms and other neurodegenerative diseases. NFX1 has been identified through a CRISPR-Cas9 screen as a gene that reduces the levels of dipeptide repeat proteins (DPRs) by lowering the nuclear export of GGGGCCC repeat-containing transcripts upon silencing (Cheng et al, 2019;Hautbergue et al, 2017). That gene was also identified through our screen as a reducer of a-synuclein spread upon silencing, presumably through lowering intracellular levels of a-synuclein, thereby having a consistent directionality of effect as reported in that c9orf72 screen.…”
Section: Discussionsupporting
confidence: 63%
“…Several of the identified genes have been previously linked to the pathogenesis of parkinsonisms and other neurodegenerative diseases. NFX1 has been identified through a CRISPR-Cas9 screen as a gene that reduces the levels of dipeptide repeat proteins (DPRs) by lowering the nuclear export of GGGGCCC repeat-containing transcripts upon silencing (Cheng et al, 2019;Hautbergue et al, 2017). That gene was also identified through our screen as a reducer of a-synuclein spread upon silencing, presumably through lowering intracellular levels of a-synuclein, thereby having a consistent directionality of effect as reported in that c9orf72 screen.…”
Section: Discussionsupporting
confidence: 63%
“…5A-E). Recent studies have suggested that a reduction in DPR levels can mitigate stressor induced cell death and restore functional NCT in iPSNs (Cheng et al, 2019). However, this study did not evaluate the effects of DDX3X manipulation on NPC components themselves but was limited to the distribution of fluorescent shuttle proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Typically, potential therapies aim at the downstream effects arising from repeat expansion to reduce their toxic consequences. The goal is to either reverse gene silencing (70,81,469,(503)(504)(505) or alleviate adverse effects of toxic RNA (98, 101, 203, 506 -514) and/or toxic proteins (98,101,203,506,515). These methods, while worthy and promising, warrant several caveats.…”
Section: Can Reds Be Cured?mentioning
confidence: 99%